THE INFLUENCE OF COMPENSATION AND MOTIVATION ON EMPLOYEE PERFORMANCE AT THE ISLAMIC EDUCATION FOUNDATION (IEF) SIRNAMISKIN ISLAMIC BOARDING SCHOOL - Azzahra, Vilda Aprisa; Wahyuningtyas, Ratri (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This research emphasizes the vital role of teachers within the education system, specifically at the Islamic Education Foundation (IEF) Sirnamiskin Islamic Boarding School, and explores how compensation and motivation influence their performance. The study aims to evaluate compensation, motivation, and employee performance, along with the effects of compensation and motivation on performance. Compensation and motivation are the independent variables, while employee performance is the dependent variable. Utilizing a quantitative research approach with Stratified Random Sampling and Partial Least Square Modelling (PLS-SEM) for analysis, the study investigates the relationships among these variables. The results indicate that both compensation and motivation are rated positively, and employee performance is also satisfactory. These results indicate that both compensation and motivation substantially influence employee performance. Hence, assessing and improving compensation and motivation at IEF Islamic Boarding School Sirnamiskin is essential for further enhancing teacher performance.